Primary Hemophagocytic Lymphohistiocytosis in an Infant - A.I. Kozhemiaka; V.A. Klymenko; V.P. Kandyba; O.V. Piontkovska; T.A. Khalturyna; A.V. Postnikov; M.I. Perkhun; O.A. Zorya (Zaslavsky O.Yu., 2014)
The paper considers the results of a clinical observation of an infant with hemophagocytic lymphohistiocytosis complicated with spontaneous splenic rupture. There were discussed the questions on diagnosis according to Histocyte Society, 2004.